Altmetrics as new indicators of scientific impact (Journal of EAHIL, 2016)
In recent years, researchers and academics in growing numbers are starting to move their everyday work onto the Web, exploring new ways to spread, discuss, share and retrieve information outside of the traditional channel of scholarly publishing. As scholarly communication moves increasingly online, there is a growing need to improve the ways in which the impact of scientific research output is evaluated. Altmetrics, even if they are still in an early stage, have the potential to develop as complements to traditional metrics and to provide a useful insight into new impact types not included in existing measures. This paper summarises the major trends, opportunities and challenges of these new metrics for both researchers and academic research libraries.